Language Assessment Practice in Hybrid Classes: Students’ Perspectives - Jabu, Baso; Asriati, Asriati; Aeni, Nur (Seminar Nasional LP2M UNM, 2023)
Abstract. This article presents the students’ perspective on the language assessment practice in hybrid classes using a survey research method. Preservice English teachers were chosen purposively as respondents in particular the ones that have passed Language Assessment or Language Testing subject. The respondents show positive views on the language assessment practice in hybrid classes. The result also reveals the role and importance of technological advancement in the process of assessing the language in hybrid classes. Keywords: Language Assessment, Hybrid Class, Students’ Perspectives